Keys and Tensions in Argentina’s Foreign Trade Policy Strategy in the Search for an "Smart Insertion into the World" (2015-2018) - Zelicovich, Julieta (Latin American Journal of Trade Policy, 2019)
After 12 years of Kirchnerist administrations, the government of Mauricio Macri have imparted substantial changes in the Argentinean foreign and economic policy. These changes have been reflected in a redesign of the foreign trade policy. We wonder what have been the characteristics of this policy during “Cambiemos” administration. In light balance of payments data, why have the results regarding the country’s external trade insertion been limited? For this purpose, the paper analyzes the principles, objectives and actions implemented, as well as the articulation of internal and external constraints (or variables) in this government, between December 2015 and October 2018. It is argued that the foreign trade policy has faced a context that was not very permissive, and fell prey to foreign policy’s "bad diagnosis" of the international context; and that this, articulated with the political and economic contradictions that occurred at the domestic level, acted to the detriment of the objectives set for a “smart international insertion”.